Fragile Histidine Triad (FHIT) Suppresses Proliferation and Promotes Apoptosis in Cholangiocarcinoma Cells by Blocking PI3K-Akt Pathway - Qiang Huang; Zhen Liu; Fang Xie; Chenhai Liu; Feng Shao; Cheng-lin Zhu; Sanyuan Hu (The Scientific World Journal)
Fragile histidine triad (FHIT) is a tumor suppressor protein that regulates cancer cell proliferation and apoptosis. However, its exact mechanism of action is poorly understood. Phosphatidylinositol 3-OH kinase (PI3K)-Akt-survivin is an important signaling pathway that was regulated by FHIT in lung cancer cells. To determine whether FHIT can regulate this pathway in cholangiocarcinoma QBC939 cells, we constructed an FHIT expression plasmid and used it to transfect QBC939 cells. Protein and mRNA expression were measured by western blotting and qRT-PCR, respectively. The viability and apoptosis of QBC939 cells were then assessed using MTT assays and flow cytometry. Our results revealed that the expression of survivin and Bcl-2 was downregulated, and caspase 3 was upregulated, in cells overexpressing FHIT. In addition, FHIT suppressed the phosphorylation of Akt. The changes in cell proliferation and apoptosis were obvious in cells overexpressing FHIT which parallels that of treatment with LY294002, a potent inhibitor of phosphoinositide 3-kinases. Treatment with LY294002 further decreased the expression of survivin and Bcl-2 and increased caspase-3 levels. These results suggest that FHIT can block the PI3K-Akt-survivin pathway by suppressing the phosphorylation of Akt and the expression of survivin and Bcl-2 and upregulating caspase 3.